Proceedings of the 2016 5th International Conference on Sustainable Energy and Environment Engineering (ICSEEE 2016) 2016
DOI: 10.2991/icseee-16.2016.115
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Life Cycle Assessment of Typical Wood base Furniture

Abstract: Abstract. The assessment of environmental performance was carried out to identify the environmental impact of three typical solid wood based furniture: A beech wood desk (P1), A white oak-and-fabric sofa (P2), A rubber wood wardrobe (P3). A field research of company' s manufacturing plant was conducted in order to investigate the production process as well as collect the inventory data under assessment. Life cycle environmental impact were assessed throughout subjects' life cycle by utilizing LCA software tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
12
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 6 publications
9
12
1
2
Order By: Relevance
“…Many LCA studies have shown that wooden products generally have favorable environmental profiles as compared with other competing products such as plastics, concrete, steel and iron (Glover et al, 2002;Werner and Nebel, 2007). Many studies have been conducted on LCA of wooden furniture in other countries of the world such as Europe (González-García et al, 2009a), China (Wang et al, 2016), Germany (Wenker et al, 2018), and Brazil (Medeiros et al, 2017). González-García et al (2012) conducted a comprehensive study on environmental profile of a wooden childhood furniture to propose an effective benchmark for its eco-labeling.…”
Section: Goal and Scope Definitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many LCA studies have shown that wooden products generally have favorable environmental profiles as compared with other competing products such as plastics, concrete, steel and iron (Glover et al, 2002;Werner and Nebel, 2007). Many studies have been conducted on LCA of wooden furniture in other countries of the world such as Europe (González-García et al, 2009a), China (Wang et al, 2016), Germany (Wenker et al, 2018), and Brazil (Medeiros et al, 2017). González-García et al (2012) conducted a comprehensive study on environmental profile of a wooden childhood furniture to propose an effective benchmark for its eco-labeling.…”
Section: Goal and Scope Definitionmentioning
confidence: 99%
“…The data was analyzed by using SimaPro v8.5 (Wang et al, 2016;Mirabella et al, 2014). This software was developed by PRé-Consultants (González-García et al, 2011).…”
Section: Life Cycle Impact Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…When designing furniture, it is essential to define the most impacting components, like seatback for chair, and reduce the dimension (Laemlaksakul and Sangsai, 2013), e.g. reducing the thickness by conducting Finite Element Analysis (Wang, Su and Zhu, 2016). Advanced technology in the production processes could improve eco-efficiency by minimizing raw materials (Ika Rinawati et al, 2018).…”
Section: Life Cycle Design (Lcd) Level Innovationmentioning
confidence: 99%